SEDIMENT TRANSPORT MODELING OF LAYOUT LOCATION AND DESIGN FOR UJUNGPANGKAH LOGISTICS TERMINAL PORT - Khasogi, Arfansyah
The purpose of this study is to determined port layout location and design recommendations at Delta Pangkah, Ujungpangkah. Delta Pangkah is one of the estuaries of Bengawan Solo River. Recommendations are obtained from the results of sediment transport modeling analysis. Modeling is simulated by numerical methods with the help of Delft 3D Flow software. Modeling is simulated using two scenarios, the existing scenario and the harbor basin scenario with duration of 1 year. Based on the result of existing scenario, the sedimentation rate at Delta Pangkah is 2.009 m/year and at north of Delta Pangkah is 0.182 m/year. The slower sedimentation rate at north of Delta Pangkah becomes the initial location of the harbor basin in next scenario. The harbor basin consists of turning area and channel. Based on the result of harbor basin scenario, the sedimentation rate at turning area is 0.223 m/year and at channel is 0.090 m/year. These are indicated by the final depth at the end of simulation is 7.777 m at turning area and 7.910 m at channel. These depths are still deeper than the harbor basin minimum depth, which is 7 m. It is concluded that the location at north of Delta Pangkah is the recommendation location and design layout for port at Delta Pangkah, Ujungpangkah.